Implementasi Quizizz Dalam Pembelajaran - Secha, Maulidin Nur; Setyowati, Setyowati; Darmanto, Eko (Peneliti.net, 2024)
This research aims to analyze the application of artificial intelligence quizizz in education. The type of research used is qualitative research with a descriptive approach. Data collection was carried out by researchers using documentation studies collecting journals that were appropriate to the research variables. Data analysis carried out in this research includes data reduction, data presentation and drawing conclusions. The results of the research obtained data showing that quizizz artificial intelligence has a big role in education. Quizizz provides convenience for teachers and students. Teachers make learning, assessment and feedback easier. Meanwhile, students are given new experiences related to assessments using the internet network. The conveniences provided by AI make learning student-centered. Learning becomes more effective, innovative and fun.